The Effect of Economic Conditions on Cardiovascular Disease - Dagný Ósk Ragnarsdóttir 1988- (2012)
The relationship between economic conditions and health has been widely researched, but the literature shows mixed results. In this paper the relationship between cardiovascular disease and economic conditions is used, with focus on changes caused by the Icelandic economic collapse in 2008. Furthermore, potential mediators in this relationship are looked at. The data used come from the health and lifestyle survey “Heilsa og líðan Íslendinga“, which was carried out by the Public Health Institute of Iceland in 2007 and 2009. The sample is a stratified random sample of 9,807 individuals 18-79 years old and a total of 42.1% answered the questionnaire in both 2007 and 2009. Logit analyses were used to examine if there was a relationship between economic conditions and the probability of having a cardiovascular disease or condition. The crisis is positively related to hypertension and total cardiovascular disease in males but no statistically significant relationship was found for females. The mediation analyses indicate mediation through changes in working hours and stress level for males in the relationship between the crisis and hypertension, and between the crisis and total cardiovascular disease. For males, changes in income partly explain the increased probability of having any cardiovascular disease or condition after the crisis. Samband efnahagsástands og heilsu hefur verið töluvert rannsakað, en niðurstöður þessara rannsókna eru ekki einróma. Sumir halda því fram að heilsa versni í uppsveiflum á meðan aðrir vilja meina að heilsa sé verri í niðursveiflum. Í þessari rannsókn er samband íslensku efnahagskreppunnar og hjartasjúkdóma skoðað. Ennfremur eru möguleg miðlunaráhrif könnuð. Gögnin sem notast er við eru fengin úr heilsu- og lífstílskönnuninni „Heilsa og líðan Íslendinga“ sem framkvæmd var af Lýðheilsustöð árin 2007 og 2009. Úrtakið er lagskipt tilviljanakennt úrtak 9.807 einstaklinga á aldrinum 18-79 ára og samtals svöruðu 42,1% upphaflega úrtaksins könnuninni bæði árið 2007 og árið 2009. Logit ...